2018
DOI: 10.1039/c8qo00433a
|View full text |Cite
|
Sign up to set email alerts
|

Pd-catalyzed carbonylation of aryl C–H bonds in benzamides with CO2

Abstract: Herein, we report the first Pd-catalyzed carbonylation of unactivated aryl C–H bonds in benzamides under 1 atm of CO2 to directly afford important phthalimides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…In 2018, Yu and co‐workers reported the first [Pd(tfa) 2 ]‐catalyzed (TFA=trifluoroacetate) benzamide‐directed carbonylation of unactivated aryl C−H bonds with atmospheric CO 2 to afford a series of phthalimides (Scheme a) . Mechanistic investigations suggested that the palladacycle might be an active intermediate, which further reacted with CO 2 to generate the desired product.…”
Section: Carboxylation Of C(sp2)−h Bonds With Co2mentioning
confidence: 96%
“…In 2018, Yu and co‐workers reported the first [Pd(tfa) 2 ]‐catalyzed (TFA=trifluoroacetate) benzamide‐directed carbonylation of unactivated aryl C−H bonds with atmospheric CO 2 to afford a series of phthalimides (Scheme a) . Mechanistic investigations suggested that the palladacycle might be an active intermediate, which further reacted with CO 2 to generate the desired product.…”
Section: Carboxylation Of C(sp2)−h Bonds With Co2mentioning
confidence: 96%
“…This type of reaction can be employed for utilizing low-value and nontoxic carboxylic acids as sustainable resources in C–C bond formation processes such as arylations or olefinations. , Regarding the utilization of CO 2 , various aromatic carboxylic acids are desirable target compounds, due to their wide application in pharmaceuticals and other high-value compounds. , There are plenty of examples using CO 2 as a carbon source in homogeneously catalyzed carboxylation reactions on preactivated arenes, such as organo-zinc or -boron compounds or aryl (pseudo)­halides. Yet, to achieve high atomic efficiency, the direct catalytic carboxylation of non-preactivated arenes is very desirable to stay in line with the principles of green chemistry. In the last decade, among others, the groups of Hou, Nolan, and Iwasawa were able to realize catalytic direct carboxylation of arenes which still require strongly electron withdrawing substituents, directing groups at the aromatic compound, or addition of stoichiometric amounts of organometallic reagents. Insertion of CO 2 into metal–aryl bonds is always a key step of these transformations.…”
Section: Introductionmentioning
confidence: 99%
“…In alternative protocols, CO was replaced by a more benign N , N ‐dimethyloxamic acid giving lower yields and using diethyl azodicarboxylate (DEAD) instead of CO led to the product resulting from ortho ‐C−H ethoxycarboxylation (R‐CO 2 Et) with the same anilide site‐selectivity . A reversed site‐selectivity with a palladium catalyst was reported using CO 2 in a poor yield . In this case, an intramolecular reaction cascade occurred leading to N ‐phenylphthalimide (Scheme ).…”
Section: C−c Bond‐forming Reactionsmentioning
confidence: 99%